New perspectives on ‘warming–wetting’ trend in Xinjiang, China - Qian Wang (Advances in Climate Change Research, 2020)
Recently, a hot topic about warmer and wetter climate change in the arid region of Northwest China, especially in Xinjiang, has attracted much attention by general public and scientific community. This study revisits this topic especially for Xinjiang in the Eurasian continental context from multiple perspectives based on most updated CRU high-resolution grid data and China's homogenized station data in 1961–2019. We conclude that such ‘warming–wetting’ trend is not a regional phenomenon for Xinjiang but has much larger spatial scale. Regions having experienced both temperature and precipitation increases reflecting ‘warming–wetting’ trend account for more than half of the Eurasian continent since 1961. Nevertheless, the ‘warming–wetting’ trend in Xinjiang suggests some unique regional features in response to the global warming. Although drought seems to have relieved to some extent, especially in the mountainous regions in western Xinjiang, the nature of arid and semi-arid climate regime has not changed. Noticeably, the interannual variability of precipitation has enlarged and the increase in extreme precipitation events has a major contribution. These findings suggest that ‘warming–wetting’ trend in Xinjiang is asymmetric regarding warming and wetting in seasons and intensifying interannual variability and increasing contribution of extreme precipitation to the total. Thus, the current ‘warming–wetting’ trend in Xinjiang possibly brings us some beneficial impacts for the ecosystem but also increases challenges for water resources utilization and risk management.